2000
DOI: 10.1007/s004410050011
|View full text |Cite
|
Sign up to set email alerts
|

Cytological changes during bioluminescence production in dissociated photocytes from the ophiuroid Amphipholis squamata (Echinodermata)

Abstract: Bioluminescence in the ophiuroid Amphipholis squamata is produced by photocytes located within the spinal ganglia of arm spines. Ganglionic cells were dissociated (pronase digestion) and photocytes separated from other cell types by using a continuous density Percoll gradient. Aliquots from a stock suspension of photocytes in artificial sea water were stimulated to produce light by using KCl or acetylcholine and fixed for ultrastructural observation at different times of the luminous process. Preluminescent, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The photocyte bioassay uses isolated light-producing cells from an osmoconforming invertebrate. Seawater is therefore the best medium in which photocytes can be maintained (Deheyn et al, 2000a). The artificial seawater medium used in this study approaches the salt composition and physicochemical properties of natural seawater, which has an average ionic strength of 0.611 (0.511-0.650 range; 0.61 in the bioassay; Turner et al, 1981;Atkinson and Bingman, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The photocyte bioassay uses isolated light-producing cells from an osmoconforming invertebrate. Seawater is therefore the best medium in which photocytes can be maintained (Deheyn et al, 2000a). The artificial seawater medium used in this study approaches the salt composition and physicochemical properties of natural seawater, which has an average ionic strength of 0.611 (0.511-0.650 range; 0.61 in the bioassay; Turner et al, 1981;Atkinson and Bingman, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Photocyte isolation was based on the method of (Deheyn et al, 2000a). In summary, 3-5 brittlestars (ca.…”
Section: Photocyte Bioassaymentioning
confidence: 99%
See 1 more Smart Citation
“…The species is also bioluminescent. Bioluminescence is produced only in the arms and is attributed to specific photocytes under ganglial control (Deheyn et al 2000a). It has been shown that each colour variety produces light of characteristic intensity, irrespective of the geographic origin of specimens (Deheyn et al 1997, Deheyn 1998.…”
Section: Introductionmentioning
confidence: 99%
“…In their description of the spine ligament node of Amphipholis squamata (Delle Chiaje, 1828), Deheyn et al [93] referred to the capsular cells as “type D” cells, which, like those of O . nigra , are ciliated, contain heterogeneous vacuoles and compartmentalise DCV-containing cells [93,96]. In addition they were shown to be the source of bioluminescence in A .…”
Section: Discussionmentioning
confidence: 99%